Effect of Palmyra Fruit Water–Egg Yolk Diluent with Moringa Leaf Extract on Boar Sperm Membrane Integrity and Motility - I Wayan Gorda; I Putu Gde Pradnya Nolan Toli; Wayan Bebas (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2026)
This study aimed to evaluate the effect of palmyra fruit water–egg yolk diluents supplemented with moringa (Moringa oleifera L.) leaf extract on the intact plasma membrane, intact acrosomal membrane, and motility of boar spermatozoa during liquid storage. A completely randomized design was used, with seven diluent formulations varying in concentrations of egg yolk and moringa leaf extract. Each treatment was replicated four times and stored at 15-18°C for up to 72 hours. Semen quality was evaluated at 0, 24, 48, and 72 hours of storage. Data were analyzed using analysis of variance followed by Duncan’s multiple range test. Both diluent formulation and storage duration significantly influenced all semen quality parameters (p < 0.05). The diluent containing palmyra fruit water supplemented with 20% egg yolk and 15% moringa leaf extract produced the highest membrane integrity, motility, and viability with the lowest abnormality rate. The semen maintained acceptable quality for artificial insemination for up to 48 hours of storage. The superior performance of this formulation is biologically associated with the synergistic interaction between carbohydrate-derived energy from palmyra fruit water, phospholipid-mediated membrane stabilization from egg yolk, and antioxidant protection from moringa leaf extract against oxidative stress.